Harnessing Seawater for Algae-based Omega-3 Production: Microalgal Strain Improvement and Cultivation Strategies for Achieving Commercial Robustness - Hafiza Aroosa Malik; Mohammed Abdullah; Ayesha Shahid; Anqi Zhao; Alexei E. Solovchenko; Abdulrahman H. Alessa; Hussain Alqahtani; Munazza Gull; Raj Boopathy; Muhammad Aamer Mehmood; Jingliang Xu (Current Pollution Reports, 2026)

Machine Learning–Enabled Microalgae Bioprocess Optimization for Alternative Foods and Water Sustainability - Muhammad Adnan Ul Haq; Mishaal Irfan; Sana Malik; Nitiphong Kaewman; Piroonporn Srimongkol; Sirasit Srinuanpan; Shaza Y. A. Qattan; Ashwaq Hassan Alsabban; Antonio Albuquerque; Raj Boopathy; Peter Ralph (Current Pollution Reports, 2026)

Advancing nano-enabled Agriculture from Precision Application To Environmental Risk and Sustainability Assessment - Jiahui Feng; Muhammad Adeel; Yukui Rui (Current Pollution Reports, 2026)

Advancing Heavy Metal Removal from Industrial Wastewater Using Oil Palm Waste–Based Adsorbent: toward Efficient Adsorption and Commercialization - Mohd Amir Asyraf Mohd Hamzah; Norhaniza Yusof; Muhammad Abbas Ahmad Zaini; Zainul Akmar Zakaria; Juhana Jaafar; Nurasyikin Misdan (Current Pollution Reports, 2025)
Purpose of Review The palm oil industry, as the largest producer of edible oil in the world, generates considerable volumes of biomass waste, including oil palm fronds, trunks, empty fruit bunches, mesocarp fibers, palm kernel shells, and palm oil fuel ash. Improper disposal of these residues contributes to environmental pollution and resource management challenges. This review aims to critically evaluate recent developments in transforming oil palm biomass waste (OPW) into low-cost, high-performance adsorbents for the removal of heavy metals from industrial wastewater, while aligning with zero-waste and circular economy goals. Recent Findings Recent studies have demonstrated that OPW-derived adsorbents, when subjected to particle size reduction and surface functionalization, exhibit significantly enhanced adsorption capacity and recovery efficiency. Notably, activated carbon nanoparticles derived from empty fruit bunch via KOH activation have demonstrated adsorption capacities exceeding 1000 mg/g for Cu 2+ and Pb 2+ , attributed to their ultrafine size and high surface reactivity. These materials also show strong reusability, with over 80% adsorption efficiency retained after multiple regeneration cycles. Integration of OPW adsorbents into dynamic systems such as fixed-bed columns, adsorption-membrane hybrids, magnetic composites, and gel matrices have been explored to improve operational stability, pollutant removal, and ease of recovery. Summary This review underscores the potential of OPW-derived adsorbents as sustainable and cost-effective alternatives for industrial wastewater treatment. The incorporation of OPW-based materials into engineered systems and the evaluation of post-treatment strategies (e.g., regeneration, reuse, safe disposal) demonstrate their applicability for real-world continuous processes. By promoting the valorization of agricultural waste and addressing current pollution control needs, these materials contribute to improved wastewater management, sustainable resource management, and industrial circularity in palm oil–producing regions. The findings offer valuable insights for environmental managers, policymakers, and industries in adopting circular economy practices and eco-friendly pollution control solutions.

Advances in Antibiotic Biodegradation: Emerging Strategies and Challenges in Mitigating Environmental Contamination and Resistance - Ibnu Maulana Hidayatullah; Soen Steven; Adi Kusmayadi; Iftita Rahmatika; Muhammad Reski; Ramaraj Boopathy; Muhamad Akmal Alfatan; Putri Wilhelmina Gusanti Purba (Current Pollution Reports, 2025)

Towards Environmental Sustainability: Employing Adaptive Laboratory Evolution to Develop Elite Algae Strains for Industrial and Environmental Applications - Mahwish Amin; Fatima Tahir; Iqra Akbar; Abdulrahman H. Alessa; Ahmad A. Alsaigh; Chen-Guang Liu; Fengxue Xin; Zhanyou Chi; Achmad Syafiuddin; Muhammad Aamer Mehmood; Raj Boopathy (Current Pollution Reports, 2025)

Biocatalytic Functionalities of Lignin Peroxidase-Based Systems in Lignin Depolymerization and Pollutants Removal from Environmental Matrices - Anil Kumar Singh; Roberto Fernandez-Lafuente; Jens Ejbye Schmidt; Grzegorz Boczkaj; Muhammad Bilal (Current Pollution Reports, 2024)
Purpose of Review In the presented review, we have summarized and highlighted recent developments in the use of lignin peroxidase (LiP) to remove a variety of pollutants from water matrices. The high redox potential of LiP is underlined by its excellent catalytic functionalities in the elimination of pharmaceuticals, phenolics, dyes, polycyclic aromatic hydrocarbons (PAHs), endocrine-disrupting chemicals (EDCs), and other miscellaneous pollutants. LiP-based computational frameworks for theoretical bioremediation of multiple pollutants have also been discussed, which have prompted a rise in scientific interest. Recent Findings According to current studies, both free and immobilized LiPs are biocatalysts capable of efficient pollutant degradation and LMW transformation. Some immobilized LiP preparations demonstrated excellent recyclability, enabling its reusability in multiple catalytic cycles. Additionally, computational degradability makes it easier to comprehend the mechanisms underlying the degradation of recalcitrant pollutants. Summary The capacity of LiP to cleave C–C and C–O–C bonds has led to its widespread application as a biocatalyst. Its outstanding potential to catalyze oxidative cleavage has been effectively used in the remediation of pollutants without needing mediators. Nevertheless, we brought attention to the current LiP system in pollutants remediation and computational framework, which has generated a significant rise in scientific interest.

Wastewater-Grown Algal Biomass as Carbon-neutral, Renewable, and Low Water Footprint Feedstock for Clean Energy and Bioplastics - Muhammad Aamer Mehmood; Mahwish Amin; Muhammad Nabeel Haider; Sana Malik; Hafiza Aroosa Malik; Md. Asraful Alam; Jingliang Xu; Abdulrahman H. Alessa; Aqib Zafar Khan; Raj Boopathy (Current Pollution Reports, 2024)

Date Palm Biochar and Date Palm Activated Carbon as Green Adsorbent—Synthesis and Application - Mona Al Malki; Abu Zahrim Yaser; Mohd. Amir Asyraf Mohd. Hamzah; Muhammad Abbas Ahmad Zaini; Nurzila Ab. Latif; Siti Halimah Hasmoni; Zainul Akmar Zakaria (Current Pollution Reports, 2023)

Removal of Toxic Metals from Water by Nanocomposites through Advanced Remediation Processes and Photocatalytic Oxidation - Ahmad Farhan; Misbah Zulfiqar; Samiah; Ehsan Ullah Rashid; Shahid Nawaz; Hafiz M.N. Iqbal; Teofil Jesionowski; Muhammad Bilal; Jakub Zdarta (Current Pollution Reports, 2023)
Purpose of Review Heavy and toxic metals are becoming more prevalent in the water sources of the globe, which has detrimental repercussions for both human health and the health of ecosystems. The summary of recent findings on treatment possibilities of toxic metal species by nanomaterials should facilitate the development of more advanced techniques of their removal. Recent Findings The high concentrations of chromium, mercury, and arsenic identified in wastewater cause a hazard to human health. There is a wide variety of nanoadsorbents and nanophotocatalysts used for heavy/hazardous metal removal. Recent research has resulted in the production of advanced nanostructures that exhibit extraordinary heavy/hazardous metal adsorption effectiveness and photocatalytic diminution of metal ions. These nanostructures have physically and chemically tunable features. Summary In this review article, the use of carbon-based nanomaterials, polymer-based nanomaterials, and semiconductor-based nanomaterials are extensively discussed to remove mercury, chromium, and arsenic ions from wastewater by the adsorption process. Advanced nanomaterials involved in photocatalytic reduction are also comprehensively discussed.

Algae-Mediated Resource Recovery from Urban Wastewater - Muhammad Usman; Mahwish Amin; Iqra Kamal; Ayesha Shahid; Jingliang Xu; Md. Asraful Alam; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf; Raj Boopathy (Current Pollution Reports, 2023)

Prospects of Multiproduct Algal Biorefineries Involving Cascading Processing of the Biomass Employing a Zero-Waste Approach - Sana Malik; Ayesha Shahid; Muhammad Nabeel Haider; Mahwish Amin; Michael J. Betenbaugh; Muhammad Aamer Mehmood; Muhammad Adnan Ul Haq; Achmad Syafiuddin; Raj Boopathy (Current Pollution Reports, 2022)

Unprecedented Impacts of Aviation Emissions on Global Environmental and Climate Change Scenario - Farooq Sher; David Raore; Jiří Jaromír Klemeš; Piyya Muhammad Rafi-ul-Shan; Martin Khzouz; Kristina Marintseva; Omid Razmkhah (Current Pollution Reports, 2021)
There has been a continuously growing trend in international commercial air traffic, with the exception of COVID-19 crises; however, after the recovery, the trend is expected to even sharpen. The consequences of released emissions and by-products in the environment range from human health hazards, low air quality and global warming. This study is aimed to investigate the role of aviation emissions in global warming. For this purpose, data on different variables including global air traffic and growth rate, air traffic in different continents, total global CO 2 emissions of different airlines, direct and indirect emissions, air traffic in various UK airports and fuel-efficient aircraft was collected from various sources like EU member states, Statista, Eurostat, IATA, CAA and EUROCONTROL. The results indicated that in 2019, commercial airlines carried over 4.5 × 10 9 passengers on scheduled flights. However, due to the COVID-19 pandemic in 2020, the global number of passengers was reduced to 1.8 × 10 9 , representing around a 60% reduction in air traffic. Germany was the largest contributor to greenhouse gas (GHG) from the EU, releasing 927 kt of emissions in 3 years. In the UK, Heathrow airport had the highest number of passengers in 2019 with over 80 million, and the study of monthly aircraft movement revealed that Heathrow Airport also had the highest number of EU and International flights, while Edinburgh had the domestic flights in 2018. These research findings could be beneficial for airlines, policymakers and governments targeting the reduction of aircraft emissions. Graphical abstract

Advances in Green Technologies for the Removal of Effluent Organic Matter from the Urban Wastewater - Ayesha Shahid; Aqib Zafar Khan; Sana Malik; Chen-Guang Liu; Muhammad Aamer Mehmood; Achmad Syafiuddin; Ning Wang; Hui Zhu; Raj Boopathy (Current Pollution Reports, 2021)

Recent Advances on Coagulation-Based Treatment of Wastewater: Transition from Chemical to Natural Coagulant - Muhammad Burhanuddin Bahrodin; Nur Syamimi Zaidi; Norelyza Hussein; Mika Sillanpää; Dedy Dwi Prasetyo; Achmad Syafiuddin (Current Pollution Reports, 2021)

Degradation of Pharmaceuticals and Personal Care Products by White-Rot Fungi—a Critical Review - Muhammad B. Asif; Faisal I. Hai; Lakhveer Singh; William E. Price; Long D. Nghiem (Current Pollution Reports, 2017)